STUDI KASUS : PROFIL SEL DARAH MERAH ANJING YANG TERINFEKSI BABESIA SP. - Yanse Yane Rumlaklak; Jois Moriani Jacob; Aven B Oematan (JURNAL KAJIAN VETERINER, 2018)
Babesia sp. is a protozoa that infects dogs through tick bite and can cause babesiosis. The purpose of blood tests in case dogs is to find out the profile of the dog's red blood cells with babesiosis. On clinical examination found many ticks on the dog's body. Dogs show clinical symptoms of dehydration and paleness in the mucosa. Blood collection is done through the anterior antibrachii cephalica vein. Blood is taken and collected in EDTA tubes. Then the examination is done by examining blood parasites, examining erythrocyte values, examining hemoglobin concentration and hematocrit values. Examination of blood parasites was done by making reticulocyte preparations, while examining erythrocyte values, hemoglobin concentration and hematocrit values were performed using a Vet Scan® HM 5TM machine. The results of examination of reticulocyte preparations showed the existence of Babesia sp infestations with a presentation of 0.68%. Erythrocyte values, hemoglobin concentration and hematocrit values were 3.52x106 // µL, 6.90 g / dL and 23.81%. Based on history, physical examination, clinical and laboratory examination, it can be concluded that the Beagle dog named Loh has microcytic hypochromatic anemia.